Factors influencing Iranian consumers' attitudes toward fast-food consumption. Issue 2 (5th February 2018) - Ghoochani, Omid M.; Torabi, Razieh; Hojjati, Mohammad; Ghanian, Mansour; Kitterlin, Miranda
Abstract : Purpose: Eating patterns around the world have changed considerably, including food choices and preparation. One of these alterations in food consumption patterns is an increase in desire for fast-food consumption, which has been associated with poor diet quality. In order to analyze consumers' food consumption behaviors, it is necessary to account for psychological factors (e.g. attitudes) that shape behaviors. Thus, the purpose of this paper is to explore influencing factors on the attitudes of consumers in Isfahan City toward fast-food consumption, so as to understand why consumers use fast-food despite widespread knowledge of the negative health consequences. Design/methodology/approach: The predominant paradigm of the present study was quantitative, in that it was a correlational survey. The population of this study consisted of consumers who lived in Isfahan city in June 2015. A total sample of 350 people was selected using convenience sampling. Data were collected through a face-to-face interview with the consumers using a researcher-made questionnaire. Analysis was conducted using SPSS (V20) and AMOS (V20) software and a set of correlation and differential tests. Findings: The results revealed that "health consciousness" and "trust" are the main effective factors on the attitudes of the respondents. The results also revealed that the elder and married respondents have more positive attitudes toward fast-food consumption. Originality/value: It is worth mentioning that fast-food has become an important part of the Iranian diet. These findings have both academic and policy implications. The results showed that the need for much more consumer education regarding fast-food and mass media could effectively be used. Further, the government should support and subsidize fast-food restaurants so that they may produce healthier food options.